Peningkatan Pemahaman Pendidikan Seksual melalui Permainan Ular Tangga di Taman Kanak-Kanak - Mamluatul Lu’lu’a (Lembaga Penelitian dan Pengabdian Institut Kariman Wirayudha Sumenep, 2023)
The research aims to: 1) determine children's understanding of sexual education before the implementation of the